Prevalence and risk factors of osteopenia in adults with short bowel syndrome: a retrospective longitudinal cohort study - Sun, Guangming; Xia, Yufei; Wang, Haoyang; Xiao, Yaqin; Zhang, Li; Zhang, Yupeng; Gao, Xuejin; Wang, Xinying (Frontiers in Medicine, 2024)
Background Metabolic Bone Disease (MBD) is common in patients with short bowel syndrome (SBS). This study was to investigate the incidence and risk factors of osteopenia in adult SBS patients. Methods Hospital records from January 2010 to December 2019 were used to identify all eligible patients. Logistic regression and a nomogram were used to analyze the data. Results A total of 120 patients with SBS were included in this study, and 76 patients (63.3%) developed osteopenia during the 10-year observation period, The multivariate analysis using the logistic regression model demonstrated that age (OR = 1.070; 95%CI: 1.016–1.126, p = 0.010), female (OR = 5.098; 95%CI: 1.211–21.456, p = 0.026), tumor history (OR = 4.481; 95%CI: 1.125–17.854, p = 0.033), duration of SBS (OR = 1.0862; 95%CI: 1.022–1.103, p = 0.002) and remnant ileum (OR = 4.260; 95%CI: 1.210–15.002, p = 0.024) were independent risk factors for osteopenia in adults with SBS. The area under the curve (AUC) for the joint model (age, female, tumor history, duration of SBS, remnant ileum) was 0.848 and the corresponding sensitivity and specificity were 0.855 and 0.705, respectively. The C-index was 0.849 (95% CI: 0.778–0.917); thus, the predictions made by the model were close to the actual outcomes. In the decision curve analysis, the nomogram performed well and was feasible to make beneficial clinical decisions. Conclusion This study reveals the high prevalence of osteopenia in SBS patients and highlights the importance of early identification and treatment of osteopenia. A nomogram may provide personalized prediction and guidance for medical intervention.